Zoomorphic Representations in Early Cycladic Art: A Catalogue Reference List - Ashbacher, Mariah (My University, 2017)
The focus of my thesis is to examine the noteworthy role that three-dimensional zoomorphic figures played in Cycladic Art during the Early Bronze Age Aegean period. The importance of animals for this period, clearly documented by their artistic representations, has largely been surpassed by scholarship on the anthropomorphic figures found in and around burial sites. It is my intention with this study, and an accompanying reference list of sixty-nine works, to provide evidence that supports the importance of the animals, their relationship to the communities of the islands, and to discuss the reasons and iconography behind their artistic production. Previously, the zoomorphic objects discussed here have been studied considering the archaeological context of their discovery, as part of a chronological group or on an individual basis only for their aesthetic qualities. However, by compiling them as an isolated corpus of objects, and then arranging them chronologically, new interpretations become apparent. When these considerations are combined with existing information known about the settlements and cemeteries where they were excavated, established hypotheses about other artifacts, and comparative data concerning cultures of contact, it is possible to come to new perspectives concerning the role of animal objects in the Early Cycladic period. I propose that the three-dimensional zoomorphic figures represented in the catalog reference list are in the categories of votives and occasionally cult images used in domestic cult activity.
Keywords: Cycladic; Zoomorphic; Bronze Age; Aegean Art